Exploring Australian pharmacists’ perceptions and practices towards reducing the risk of medicines-related harm in aged care residents - Ali, Sheraz; Curtain, Colin M.; Peterson, Gregory M.; Salahudeen, Mohammed S. (Frontiers in Pharmacology, 2023)
Background: Older people living in residential aged care facilities (RACFs) frequently experience medicines-related harm. Evidence regarding the perception and practices towards reducing these harms may facilitate the development of customised educational programs for pharmacists providing services in RACFs. Objective: To explore Australian pharmacists’ opinions and practices towards reducing the risk of medicines-related harm in aged care residents. Methods: An online survey was developed based on a literature review, expert opinion, and feedback from pharmacists providing services in RACFs. A web link for the survey was shared via professional pharmacy organisations and social media groups with Australian pharmacists providing services in RACFs. Results: A total of 209 pharmacists participated in the survey. Of these, 76% (n = 158) were residential medication management review (RMMR)/embedded pharmacists, and 24% (n = 51) were supply pharmacists for RACFs. Most pharmacists believed that medicines-related harm is common in residents (n = 174, 83%), yet few agreed that pharmacists have enough time to participate in medicines-related harm reduction services (n = 60, 28%). There was a high level of agreement regarding the key risk factors (e.g., inappropriate medicines, anticholinergic drug use, and transitions of care) and potential strategies (e.g., embedded pharmacists in RACFs, educating aged care staff, and collaborative pharmacist-led medication reviews) for reducing medicines-related harm in residents. Conclusion: Pharmacists agreed that older residents often experience medicines-related harm, but they did not frequently participate in medicines-related harm reduction services. Initiatives to engage pharmacists in team-based harm reduction services and educate aged care staff regarding safe medication management may improve residents’ safety and health outcomes.